PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN PECAHAN SISWA KELAS V SDN 1 WALUYOREJO TAHUN AJARAN 2012/2013. - Sulistiyowati, Eni (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Implementation of Cooperative Learning Model Numbered Head Together (NHT) with Concrete Media in Improving Learning Fractions 5th Grade Student of SDN 1 Waluyorejo 1 in Year 2012/2013. The study aimed to (1) describe the application of learning models, (2) describing the increase of learning, (3) describe the problems and their solutions in the implementation of Cooperative Learning Model Numbered Head Together (NHT). This research subjects is five grade the thirdteen studen of first elementary school Waluyorejo. The experiment was conducted in three cycles, with each cycle consisting of planning, action, observation and reflection. Data collection techniques with engineering tests, observations, interviews, and dokumentation. Test the validity of using triangulation. Data analytis with qualitative and quantitative. The result show the cooperative learning model Numbered Head Together (NHT) with concrete media, so as to improve fractions 5th grade student. The percentage of completeness praexecuted new student reaches 30%, after executed action on cycles I increased to 81,3%, cycles II 88,5%, and cycles III 91,5%. Keywords: Numbered Head Together, Concrete Media, Fractions Abstrak: Penerapan Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) dengan Media Konkret dalam Peningkatan Pembelajaran Pecahan Siswa Kelas V SDN 1 Waluyorejo Tahun Ajaran 2012/2013. Penelitian ini bertujuan untuk (1) mendeskripsikan penerapan model pembelajaran, (2) mendeskripsikan peningkatan pembelajaran, (3) mendeskripsikan kendala dan solusi penerapan model pembelajaran kooperatif tipe Numbered Head Together (NHT). Subjek penelitian ini adalah siswa kelas V SDN 1 Waluyorejo sejumlah 30 siswa. Penelitian dilaksanakan dalam tiga siklus, tiap siklus terdiri atas perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data dengan teknik tes, observasi, wawancara, dan dokumentasi. Uji Validitas data menggunakan metode triangulasi. Analisis data menggunakan analisis kuantitatif dan kualitatif. Kesimpulannya bahwa penerapan model pembelajaran kooperatif tipe Numbered Head Together (NHT) dengan media konkret dapat meningkatkan pembelajaran pecahan siswa kelas V SD. Pada pratindakan persentase ketuntasan siswa 30%, setelah dilaksanakan tindakan pada siklus I meningkat menjadi 81,3%, siklus II 88,5%, dan siklus III 91,5%.   Kata kunci: Numbered Head Together, Media Konkret, Pecahan.